KAJIAN EKONOMI HARGA POKOK PRODUKSI DAN PEMASARAN GLASIR FG15 SUHU 1.250 FORUM MANAJEMEN, Volume 11, Nomor 1, Tahun 2013 O C – 1.300 C SERTA PENGARUHNYA TERHADAP HARGA JUAL DAN KEPUTUSAN BISNIS PADA UPT PSTKP BALI – BPPT - I Nyoman Normal (Forum Manajemen, 2013)
Glazur is a material that simialiar of thin mirror and will trickle withbodies if it ï¬ red at high temperature. Basic glazur must have the same expantiontemperature as the bland, so if it ï¬ red its glazur did not crack. The aims of this researchthat relate of FG15 glazur were : (1) To calculate cost of goods manufactured; (2)To identify marketing mix; (3) To determine cost price; and (4) To know usefull ofstandard costing for business decision. The research results that relate of FG15glazur were : (1) Cost of goods manufactured was Rp 24.127,71, that followed by :raw material cost Rp 1.414,95, direct labour cost Rp 11.632,37, variable overhead cost Rp 7.215,91, and ï¬ xed overhead cost Rp 3.864,48 ; (2) The marketing mix was not applicated by commercial, the component of marketing mix that followed byproduct, price, distribution, and promotion still minimal and simple; (3) The sellingprice was Rp 27.746,87 each liter, that followed by : cost of goods manufacturedRp 24.127,71, expected proï¬ t margin Rp 1.206,38, operating expense Rp 2.412,77(marketing expense Rp 1.447,66 and general & administartion expense Rp 965,11);and (4) Standard cost application is very usefull into business decision for FG15glazur, that is : a) As a tool of performance and cost control into produce of FG15Glazur(such as : marketing manajer performnace, production manajer performance,raw material cost, direct labor cost, etc) , b) As a tool of sell pricing and transferpricing decision of FG15 glazur (such as : selling price, transfer price, inventoryvalue, etc); c) As a tool of rasional cost measurement of FG15 glazur (such as : costof goods manufactured, operating expense, etc), and d) As a tool of recording costeconomizing that related of FG15 glazur (if compare with actual cost).